Thil Ulenspiegel et Philippe II d’Espagne en Grande Guerre - Marine Branland (Astérion)
From the 16th to 19th and again in the 20th century, Till Eulenspiegel weaved his way through time and history. He became a legendary character of the Dutch Revolt embodying the freedom against the persecutions of Philip II of Spain in Charles De Coster’s version (1867) and the tale was given new significance during the First World War. Two Belgian artists (Paul-Auguste Masui-Castricque and Walter Vaes) referred to the legend in their engravings to deliver a message on the ongoing war. By thinking about time and cultural parallelisms, this paper seeks to understand the stakes of evoking the Legend during the war and also after as do Romain Rolland – writing the preface to a German translation of the Legend in 1926 – and two other Belgian artists illustrating Charles De Coster’s text during the 1920s: Maurice Langaskens and Frans Masereel.